Understanding student preferences for ready-to-eat meals: evaluating consumption habits and enhancements for the menu Rahmah initiative at UiTM - Affendy Lee, Noor Azli; Rozli@Rosli, Mohd Ikmal Fazlan; Abd Ghani, Kay Dora; Sulaiman, Suria; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2024)
The research explores university students' insights on ready-to-eat meals, with a focus on their consumption habits, pricing perceptions, and preferences. The study aims to identify key factors influencing students' decisions to consume ready-to-eat meals and their views on the in-campus Menu Rahmah initiative. A survey was administered to students from a northern Universiti Teknologi MARA (UiTM) campus, collecting data on their familiarity with ready-to-eat meals, consumption frequency, sources of information, and factors influencing their purchasing decisions. The survey also gathered opinions on potential improvements to the Menu Rahmah program and the likelihood of recommending it to others. Results indicate that a significant portion of students are familiar with ready-to-eat meals, primarily learning about them through online advertisements, supermarkets, and social media. Despite their familiarity, the frequency of consumption varies, with many students reporting rare to occasional use. Key factors influencing their purchasing decisions include price, quality, variety, and dietary preferences. Students suggested several improvements to the Menu Rahmah initiative, such as enhancing food quality, increasing portion sizes, and improving availability and accessibility. Additionally, there is a strong consensus on the need for better awareness and promotion of the program. In conclusion, the study provides valuable insights for university administrators and policymakers to refine and expand ready-toeat meal services, ultimately contributing to better student nutrition and convenience.